Discipline, culture and community in writing: getting specific with EAP - Ken Hyland (Scripta Manent)
It is almost a cliché now to say that writing (and reading) are not abstract skills but only make sense within wider social and cultural practices. This means that we must see the social context of an event as more than just the immediate environment surrounding it. We have to look beyond specific acts of writing to recognise how wider institutions and social groups influence them. We must, in other words, see communities as cultures. Culture is a key dimension of writing and of writing differences, and it can influence every aspect of language use. In this paper I will explore some of the ways that disciplinary cultures influence writing in academic contexts by looking at repeated patterns of language choices as evidence of specific cultural beliefs and practices. I discuss some data which supports the importance of specificity by drawing on some of my research over the last decade, arguing that identifying the particular language features, discourse practices, and communicative skills of target groups is central to teaching English in universities.